From Pablo Honey to A Moon Shaped Pool: Radiohead’s Experimental, Political Journey - Guillaume Clément (Revue LISA)
Radiohead are often credited as one of the most avant-garde rock bands in Britain, having both bent and expanded the boundaries of this genre beyond its traditional definition as guitar-based music. While their first two LPs largely stuck to existing trends in the rock music of the time, OK Computer (1997), a more experimental effort met with commercial success, is often singled out as their career-defining album. As their music became more complex, Radiohead evolved into a politicized band as well, with singer and songwriter Thom Yorke seeking inspiration in the socio-political context of the time. OK Computer can thus be seen as the album which paved the way for three key characteristics of Radiohead’s music to this day: the inclusion of more experimental influences in their brand of rock music, the subversiveness of politically-laden lyrics, and a creative approach as to the way music is to be marketed and consumed.